Pengembangan Media Pembelajaran Interaktif dengan Pemanfaatan Augmented Reality (AR) pada Materi Desain Grafis Kelas XI DKV Smkn 2 Wonosari - Alamsyah Nur Muslimin; Priyanto (Department of Electronics and Informatics Engineering Education, 2025)
This research aims to: (1) develop interactive learning media to help students of class XI DKV learn graphic design material at SMKN 2 Wonosari. (2) test the feasibility of interactive learning media on graphic design material through the alpha and beta test process. This research uses the Research and Development (R&D) research method and uses the Allesi & Trolip development model. The stages of this research are Planning, Design, and Development. The interactive learning media testing process uses 2 test stages, namely alpha test and beta test. The alpha test process was carried out by 2 material experts and 2 media experts. The beta test process was carried out by students of class XI DKV SMKN 2 Wonosari, totaling 34 students. This research obtained the following results: (1) The interactive learning media developed contains text and video material and additional Augmented Reality (AR) features that can help DKV XI class students in learning graphic design material at SMKN 2 Wonosari. (2) From the results of the alpha test conducted by material experts and media experts obtained a feasibility percentage of 85.5% and 85.26% so that it is in the very feasible category, from the results of the beta test conducted by students of class XI DKV SMKN 2 Wonosari obtained a feasibility percentage of 88.12% so that it is in the very feasible category.